2012
DOI: 10.1111/j.1365-2648.2012.06075.x
|View full text |Cite
|
Sign up to set email alerts
|

Resident strategies for making a life in a nursing home: a qualitative study

Abstract: Aim To identify strategies that older adults use to adapt to live in long‐term care. Background The use of long‐term care services has risen and this trend is expected to continue as the population reaches old age. Moving into a long‐term care setting has been documented internationally as an overwhelming life change for many older adults. It has been observed that residents adjust differently over time, but the basis for these differences needs further exploration. Design A qualitative design using grounded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 32 publications
(73 reference statements)
3
80
0
1
Order By: Relevance
“…Another study on resident strategies for making a successful life in an NH (Brandburg et al . ) introduced the theme of ‘personal resilience,’ which is similar to this study's theme, ‘seeing residents’ potential’. Similar to our results regarding nurses’ perspectives on encouraging residents’ self‐care, indicated by the theme ‘writing a personalised chart about each resident's habits, abilities, and needs,’ was the theme ‘conundrum of collaboration’ identified by Singleton (), which reflected the multidisciplinary nature and institutional focus of care.…”
Section: Discussionmentioning
confidence: 91%
“…Another study on resident strategies for making a successful life in an NH (Brandburg et al . ) introduced the theme of ‘personal resilience,’ which is similar to this study's theme, ‘seeing residents’ potential’. Similar to our results regarding nurses’ perspectives on encouraging residents’ self‐care, indicated by the theme ‘writing a personalised chart about each resident's habits, abilities, and needs,’ was the theme ‘conundrum of collaboration’ identified by Singleton (), which reflected the multidisciplinary nature and institutional focus of care.…”
Section: Discussionmentioning
confidence: 91%
“…Brandburg et al (), Iwasiw et al (), Lee (), Lee et al (), Reed and Payton (), Sussman and Dupuis ()…”
Section: Resultsunclassified
“…Lee () found that greater perceived emotional support from co‐residents ( β = 0.342, p < 0.001) and staff ( β = 0.220, p < 0.01) predicted better adjustment to relocation. New connections and relationships seemed to be facilitated by older people having a positive attitude to get along with others (Brandburg et al, ; Falk et al, ; Lee et al, ), joining buddy groups, and taking on advocate and mentor roles to support co‐residents (Hersch et al, ). Establishing new connections and relationships with co‐residents also seemed to be facilitated by factors such as: involvement in the decision to move into the care facility (Iwasiw et al, ); introductions to co‐residents by resident mentors (Reed & Payton, ); family members actively encouraging and facilitating new social networks in the care facility (Davies & Nolan, ; Sandberg et al, ); and older people engaging with meaningful activities and events such as exercise, music, games, and religious activities and services (Brandburg et al, ; Ellis & Rawson, ; Falk et al, ; Hersch et al, ; Iwasiw et al, ; Sussman & Dupuis, ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the older adults in this quadrant tended to have lived in LTC facilities for the longest time. Studies that explored how older adults adapt to LTC living have pointed out that in‐person visits to LTC facilities and decision‐making of moving into LTC facilities are conducive to the adaptation of older adults to living in the LTC facilities . Although the present study could not assess the decision‐making process in the older adults, in‐person visits to LTC facilities seems to be the key influence on the decision‐making of older adults to move into an LTC facility.…”
Section: Discussionmentioning
confidence: 64%